“Anxiety or enjoyment, I feel pleasant to welcome them both”: thematic analysis of a Chinese PhD student’s personal growth experiences - Chen, Hua (Frontiers in Psychology, 2023)
Engaging with research is an emotionally demanding experience and a trajectory full of difficulties, challenges, and stress. This autoethnographic study explored my personal experiences as a PhD student in a four-year program and conducted a qualitative thematic analysis by analyzing 550 research diary entries collected between September 2018 and June 2022, in which supervisor feedback and reviewer comments were part of the content. Three recurring, unique, and salient themes pertaining to my personal experiences were identified: being fraught with anxiety, gaining a sense of enjoyment, and achieving personal growth. Whereas anxiety was from publication and dissertation writing, foreign language writing, and individual stressors, enjoyment was gained from the support network and conducting research. My personal growth was reflected from sustained engagement and improved autonomy. In the process, I experienced some negative emotions, but found more enjoyment. The findings indicate that anxiety and enjoyment are fluctuating, co-occurring, and reciprocal. The findings call for more attention to the role of research diary writing in scaffolding PhD research, providing emotional support, and facilitating personal growth and well-being of PhD students.